The viewpoints of pupils regarding post-16 education and training opportunities: a Q methodology study - Rayne, Christa Danielle (2020)
The drive to improve outcomes for all children beyond the age of 16 has been a focus of the political agenda in the UK for several decades. Research in the area has suggested that compelling children to remain in education or training until the age of 18 can promote their academic outcomes and employability (Department for Education and Skills, 2007a). The Education and Skills Act 2008 consequently raised the age of compulsory education or training to 18. This change has, however, not been without challenge and a number of parties have raised particular concerns that the voices of children are not being heard on the matter (Widdowson, 2018) and that policymakers do not have a clear understanding of children’s needs in this regard.